Suicidal planning associated factors in students from a School of Nutrition in Lima, Peru, 2009 - Virú-Loza, Manuel André (2013)
Introduction: Suicidal planning is a previous step to suicide. High rates of suicidal planning among university students have been found in different populations, even higher than in the population students come from. Objectives: To determine which factors are associated with suicidal planning in students from a School of Nutrition. Design: Cross-sectional study. Institution: School of Nutrition, San Fernando Faculty of Medicine, Universidad Nacional Mayor de San Marcos. Participants: First to fourth academic year students of Nutrition. Interventions: A survey was carried out. Main outcome measures: Statistical significance in logistic regression tests. Results: In bivariate analysis none of the studied variables was associated with suicidal planning. In analysis adjusted to socioeconomic variables difficulty to fall asleep at night showed association (p=0.044). Difficulty to fall asleep at night kept its association in analysis adjusted to all variables (p=0.039). Conclusions: Difficulty to fall asleep was a significant independent risk factor of suicidal planning in students from the Nutrition School studied.